Ureaplasma urealyticum and Mycoplasma hominis urogenital infections associate with semen inflammation and decreased sperm quality. Issue 1 (10th January 2023) - Paira, Daniela A; Olivera, Carolina; Tissera, Andrea D; Molina, Rosa I; Olmedo, José J; Rivero, Virginia E; Saka, Héctor A; Motrich, Ruben D
Abstract: Ureaplasma urealyticum and Mycoplasma hominis are among the most prevalent sexually transmitted infections proposed to induce urogenital inflammation and impair sperm quality. However, the topic remains controversial since contradictory findings have been reported. Herein, we performed a comprehensive analysis of U. urealyticum and M. hominis urogenital infections and their association with urogenital inflammation (i.e., leukocyte subsets and inflammatory cytokines in semen, ) and sperm quality parameters in a cohort of men with couple's primary infertility undergoing initial infertility evaluation or with lower urinary tract symptoms and no infertility-related complaints. Overall, U. urealyticum and M. hominis infection was detected in 17.0% and 23.6% of patients, respectively, whereas the coinfection was detected in 3.8% of patients only. Remarkably, similar infection frequencies were found in the different patient subpopulations analyzed. Moreover, infections were associated with elevated semen levels of TNF, IL-1β, and IL-6 and/or increased counts of total leukocytes and their subsets, including CD4 and CD8 T lymphocytes and neutrophils. In addition, M. hominis infection and the coinfection with U. urealyticum were associated with impairments in sperm quality variables. Our results indicate that U. urealyticum and M. hominis male urogenital infections induce urogenital inflammation and decrease sperm quality, thus impairing male fertility potential. Screening for U. urealyticum and M. hominis infections and performing a comprehensive analysis of different leukocyte subsets and inflammatory cytokines in semen may be clinically helpful in the diagnosis and follow-up of male urogenital infection. Abstract : U. urealyticum and M. hominis infections are associated with male urogenital inflammation and decrease sperm quality.